The Importance of Human Resource Skills in the Digital Industry Era - Alawiyah, Sufi; Ghozali, Syukri (Innovative: Journal Of Social Science Research, 2025)
Digital transformation has revolutionized the way organizations operate, shifting human resource (HR) skills needs from traditional to digital. Skills such as digital literacy, data analysis, virtual communication and adaptive leadership are key to maintaining organizational competitiveness in industry 4.0 and towards society 5.0 (Schwas, 2016). This research aims to identify the HR skills most needed in the digital industry and their development strategies in organizations. This research used a descriptive qualitative method with a literature study approach and in-depth interviews with HR managers in the technology and manufacturing sectors (Crewel, 2013). The results showed that digital competence, continuous learning, and cross-platform collaboration skills are the three main pillars of HR development in the digital era (World Economic Forum, 2020). These findings provide a foundation for organizations to formulate training and recruitment policies based on the needs of the digital industry. In conclusion, organizations must adapt quickly to develop HR competencies to avoid being left behind in the increasingly technology-based global competition.